Chronic Reproductive Toxicity Thresholds for Northern Bobwhite Quail (Colinus virginianus) Exposed to Perfluorohexanoic Acid (PFHxA) and a Mixture of Perfluorooctane Sulfonic Acid (PFOS) and PFHxA. (22nd July 2021) - Dennis, Nicole M.; Hossain, Farzana; Subbiah, Seenivasan; Karnjanapiboonwong, Adcharee; Dennis, Michael L.; McCarthy, Chris; Heron, Christopher G.; Jackson, W. Andrew; Crago, Jordan P.; Field, Jennifer A.; Salice, Christopher J.; Anderson, Todd A.
Abstract: Terrestrial toxicology data are limited for comprehensive ecotoxicological risk assessment of ecosystems contaminated by per‐ and polyfluoroalkyl substances (PFAS) partly because of their existence as mixtures in the environment. This complicates logistical dose–response modeling and establishment of a threshold value characterizing the chronic toxicity of PFAS to ecological receptors. We examined reproduction, growth, and survival endpoints using a combination of hypothesis testing and logistical dose–response modeling of northern bobwhite quail ( Colinus virginianus ) exposed to perfluorohexanoic acid (PFHxA) alone and to PFHxA in a binary mixture with perfluorooctane sulfonic acid (PFOS) via the drinking water. The exposure concentration chronic toxicity value (CTV) representative of the lowest‐observable–adverse effect level (LOAEL) threshold for chronic oral PFAS toxicity (based on reduced offspring weight and growth rate) was 0.10 ng/mL for PFHxA and 0.06 ng/mL for a PFOS:PFHxA (2.7:1) mixture. These estimates corresponded to an adult LOAEL average daily intake CTV of 0.0149 and 0.0082 µg × kg body weight –1 × d –1, respectively. Neither no‐observable–adverse effect level threshold and representative CTVs nor dose–response and predicted effective concentration values could be established for these 2 response variables. The findings indicate that a reaction(s) occurs among the individual PFAS components present in the mixture to alter the potential toxicity, demonstrating that mixture affects avian PFAS toxicity. Thus, chronic oral PFAS toxicity to avian receptors represented as the sum of the individual compound toxicities may not necessarily be the best method for assessing chronic mixture exposure risk at PFAS‐contaminated sites. Environ Toxicol Chem 2021;40:2601–2614. © 2021 SETAC